Multilayered Precoated AISI 441 for Solid Oxide Fuel Cell Interconnects. (2nd June 2015) - Lundberg, Mats W; Berger, Robert; Westlinder, Jörgen; Holmberg, Håkan
Abstract : Sandvik Materials Technology develops nanocoatings for SOFC stainless steel interconnects. In this study a multilayered PVD-coating has been investigated. Cyclic oxidation for more than 20, 000 hours at 800°C, chromium volatilization and area specific resistance studies has been conducted on three different coatings and compared with the uncoated steel, in this case AISI441 (EN 1.4509). In this work we have shown that pre-coated AISI 441 show very promising results for SOFC interconnectors at 800°C. We have studied and compared state of the art CeCo coating with a new four layered coating that shows slightly higher cumulative chromium volatilization, similar ASR values and reduced mass gain in the cyclic oxidation experiments. SEM micrographs show the multilayered the total oxide layer is less than 10 microns after more than 20, 000 hours of exposure.